2006
DOI: 10.1002/pon.1038
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term telephone therapy outcomes for breast cancer patients

Abstract: We present the results of a breast cancer clinical trial that tested two therapy interventions delivered by telephone. Women (N = 218) with Stages I, II, or III breast cancer were randomly assigned to breast cancer health education or emotional expression interventions, or to a standard care control condition. Outcome and process measures were obtained at baseline, 6-month and 13-month follow-ups. Oncology certified nurses conducted the therapies in six, 30-minute individual phone sessions. Women in the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 46 publications
0
72
0
2
Order By: Relevance
“…In accordance, the design of clinical trials testing interventions for the reduction of psychological distress in couples facing cancer-in either patients or their partnershas typically been guided by the implicit assumption that, as a population, unselected couples or individuals facing cancer are sufficiently distressed to register a benefit for intervention [4]. However, recruitment of patient samples lacking in sufficient distress to respond positively has beenintervention trials [5,6]. The risk is that psychosocial interventions will be labeled as inefficacious when they would have been shown to be efficacious when administered to a sample with greater distress [4].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, the design of clinical trials testing interventions for the reduction of psychological distress in couples facing cancer-in either patients or their partnershas typically been guided by the implicit assumption that, as a population, unselected couples or individuals facing cancer are sufficiently distressed to register a benefit for intervention [4]. However, recruitment of patient samples lacking in sufficient distress to respond positively has beenintervention trials [5,6]. The risk is that psychosocial interventions will be labeled as inefficacious when they would have been shown to be efficacious when administered to a sample with greater distress [4].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies demonstrated that patients receiving information and support can more conveniently cope with conditions causing psychological distress such as anger, hopelessness or ambiguousness. [8][9][10]13,14,22,26,27 In the literature, it has been shown that there are some changes in the feeling of identity and ego; thus, there may be a decrease in self-esteem in patients with breast cancer. [4][5][6][7]12,28 In patients with breast cancer, it is thought that this could be due experiencing alterations in body image and selfesteem with changes in their body.…”
Section: Discussionmentioning
confidence: 99%
“…Phone interviews are an effective method to provide information and support to individuals and groups in cancers as well as several chronic diseases. [9][10][11][12][13][14]22 In several studies, they was found that, by this method, the level of knowledge is increased in patient receiving chemotherapy while symptoms related to chemotherapy are decreased. 12,[23][24][25] In our study, no significant difference was found between experiment and control groups regarding mean overall anger scores obtained before training (p> 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations